Mucosal-adapted bacteriophages as a preventive strategy for a lethal Pseudomonas aeruginosa challenge in mice - Luiz Felipe Leomil Coelho; Mateus de Souza Terceti; Sergio Pereira Lima Neto; Raíne Piva Amaral; Ana Luisa Cauvila dos Santos; William Permagnani Gozzi; Bianca Andrade de Carvalho; Gustavo Aparecido da Cunha; Maria Fernanda Romboli Durante; Lais Sanchietta; Giovana Soares Marangoni; Matheus Luca Carotta Gabriel; et al. (Communications Biology)
Abstract Pseudomonas aeruginosa is an emergent threat due to the antimicrobial resistance crisis. Bacteriophages (phages) are promising agents for phage therapy approaches against P. aeruginosa. It has been proposed that metazoans harbor phages on their mucosal surfaces, and this could be exploited for the rational design of prophylactic phage therapy. The goal of this study was to evaluate the potential of phage-mucus interaction to prevent infections caused by P. aeruginosa. We isolated two phages capable of infecting P. aeruginosa. Both are similar in morphology and closely related genetically. However, phage VAC3 is more efficient in replicating in mucin-exposed P. aeruginosa in vitro and is preferentially held in the respiratory tract of C57BL/6 mice. Pre-treatment with VAC3 phage protects mice from a lethal dose of P. aeruginosa while VAC1 does not. This shows that phages adapted to mucosal conditions have potential to be applied as prophylactic measures against an ESKAPE pathogen.